In Vitro Evaluation, Chemical Profiling, and In Silico ADMET Prediction of the Pharmacological Activities of Artemisia absinthium Root Extract - Asma N. Alsaleh; Ibrahim M. Aziz; Reem M. Aljowaie; Rawan M. Alshalan; Noorah A. Alkubaisi; Mourad A. M. Aboul-Soud (Pharmaceuticals)
Artemisia absinthium L., is a plant with established pharmacological properties, but the A. absinthium root extract (AARE) remains unexplored. The aim of this study was to examine the chemical composition of AARE and assess its biological activity, which included antidiabetic, antibacterial, anticancer, and antioxidant properties. GC-MS was used to analyze the chemical components. The antioxidant activity of the total phenolic and flavonoid content was evaluated. Antibacterial activity and cytotoxic effects were identified. Enzyme inhibition experiments were performed to determine its antidiabetic potential. Molecular docking was utilized to evaluate the potential antioxidant, antibacterial, and anticancer activities of the compounds from AARE using Maestro 11.5 from the Schrödinger suite. AARE exhibited moderate antioxidant activity in DPPH (IC50: 172.41 ± 3.15 μg/mL) and ABTS (IC50: 378.94 ± 2.18 μg/mL) assays. Cytotoxicity tests on MCF-7 and HepG2 cancer cells demonstrated significant anticancer effects, with IC50 values of 150.12 ± 0.74 μg/mL and 137.11 ± 1.33 μg/mL, respectively. Apoptotic studies indicated an upregulation of pro-apoptotic genes (caspase-3, 8, 9, Bax) and a downregulation of anti-apoptotic markers (Bcl-2 and Bcl-Xl). AARE also inhibited α-amylase and α-glucosidase, suggesting potential antidiabetic effects, with IC50 values of 224.12 ± 1.17 μg/mL and 243.35 ± 1.51 μg/mL. Antibacterial assays revealed strong activity against Gram-positive bacteria. Molecular docking and pharmacokinetic analysis identified promising inhibitory effects of key AARE compounds on NADPH oxidase, E. coli Gyrase B, and Topoisomerase IIα, with favorable drug-like properties. These findings suggest AARE’s potential in treating cancer, diabetes, and bacterial infections, warranting further in vivo and clinical studies.